2022
DOI: 10.1186/s40580-022-00337-3
|View full text |Cite
|
Sign up to set email alerts
|

Ink-lithographic fabrication of silver-nanocrystal-based multiaxial strain gauge sensors through the coffee-ring effect for voice recognition applications

Abstract: Human voice recognition techniques have remarkable potential for clinical applications because information from acoustic signals can reflect human body conditions. This paper reports the fabrication of Ag nanocrystal (NC)-based multiaxial wearable strain gauge sensors by ink-lithography for voice recognition systems. Benefiting from the one-step-device-fabrication strategy of ink-lithography, which can yield Ag NC patterns with specific dimensions and endow physical properties, the Ag NC-based multiaxial strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Furthermore, it has also been reported [20] that NP strain sensors have the potential to detect acoustic vibrations with an infinitesimal amplitude, which extends the application field of NP arrays towards precision devices with ultrafast dynamics. This possibility opens the way to exploit NP strain sensors as vibration sensors, which are of interest in various application fields ranging from voice recognition [21] to condition-based monitoring (CbM) of machines, which can enable cost savings on machine life and maintenance [22]. A recent review on the use of strain sensors for vibration sensing suggested that resistive strain sensors have a potential that needs to be further investigated, due mainly to Furthermore, it has also been reported [20] that NP strain sensors have the potential to detect acoustic vibrations with an infinitesimal amplitude, which extends the application field of NP arrays towards precision devices with ultrafast dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has also been reported [20] that NP strain sensors have the potential to detect acoustic vibrations with an infinitesimal amplitude, which extends the application field of NP arrays towards precision devices with ultrafast dynamics. This possibility opens the way to exploit NP strain sensors as vibration sensors, which are of interest in various application fields ranging from voice recognition [21] to condition-based monitoring (CbM) of machines, which can enable cost savings on machine life and maintenance [22]. A recent review on the use of strain sensors for vibration sensing suggested that resistive strain sensors have a potential that needs to be further investigated, due mainly to Furthermore, it has also been reported [20] that NP strain sensors have the potential to detect acoustic vibrations with an infinitesimal amplitude, which extends the application field of NP arrays towards precision devices with ultrafast dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on the use of strain sensors for vibration sensing suggested that resistive strain sensors have a potential that needs to be further investigated, due mainly to Furthermore, it has also been reported [20] that NP strain sensors have the potential to detect acoustic vibrations with an infinitesimal amplitude, which extends the application field of NP arrays towards precision devices with ultrafast dynamics. This possibility opens the way to exploit NP strain sensors as vibration sensors, which are of interest in various application fields ranging from voice recognition [21] to condition-based monitoring (CbM) of machines, which can enable cost savings on machine life and maintenance [22]. A recent review on the use of strain sensors for vibration sensing suggested that resistive strain sensors have a potential that needs to be further investigated, due mainly to their low cost and low weight, especially when compared to accelerometers, which are currently the industry standard for vibration sensing and monitoring [23].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, crack-based sensors using various materials, such as metal, graphene, and carbon nanotube, , have shown excellent capabilities in detecting subtle vibrations. Recently, nanoparticles (NPs) have been considered promising building blocks for realizing highly sensitive strain sensors owing to their solution processability and interparticle distance-dependent transport, enabling low-cost and high-sensitivity sensor fabrication. The advancement of crack-based sensors has significantly enhanced our understanding of human voice by enabling detailed linguistic analysis through direct detection of vocal cord vibrations to the state of utilizing spectrogram. , However, the nonzero interparticle distances induce high electrical resistances, leading to large power consumption, poor readability, and low signal-to-noise ratio (SNR). Thus, a strategy to achieve excellent electromechanical performance and high signal versus voltage is urgently needed; however, relevant research is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable sensors that directly detect the vibration of vocal folds have recently gained significant attention over traditional voice-recognition systems since they maintain sensibility independent of background noise. Extensive studies have been conducted to design highly sensitive, readily readable, reliable, stable, and biocompatible wearable sensors. Piezoresistive strain sensors have been highlighted as successful candidates owing to their straightforward structure, which converts physical signals into digital data without additional circuits or attachments.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Colloidal inorganic NCs enable low-cost, facile, room-temperature, and solution-based deposition of functional inorganic thin films over large areas and have been widely used to fabricate different types of devices. 3,11,12 Among the various semiconducting NCs, metal chalcogenide and perovskite NCs have been studied heavily thus far owing to their superior optical and electronic properties. 13 For example, II-VI and IV-VI quantum dots exhibit unique sizeand shape-dependent optical and electronic properties owing to the quantum confinement effect, which enables precise engineering of the device architecture for high performance.…”
Section: Introductionmentioning
confidence: 99%